The behavior a dying-sick person: From donation to testament - ABDEDAIM , Hadjer; BOUHARARA, Nesrine (Journal of Human Sciences, 2025)
The behavior of a dying-sick person overwhelmed by fear of death, makes him act by “over” donating his money which may affect his interests and the ones of his heirs. That is why, the Islamic Sharia, was precursor in detailing its provisions, within bequest acts, particularly the donation act, which was followed by the Algerian legislator by the terms of his articles. It became necessary to study the behavior of the dying-sick person by both jurisprudence and law to identify the ambiguity and the impact on his behavior, changing it into a testament to protect the other’s rights from any loss.